Direct Photocatalytic Synthesis of Medium‐Sized Lactams by C−C Bond Cleavage - Wang, Na; Gu, Qiang‐Shuai; Li, Zhong‐Liang; Li, Zhuang; Guo, Yu‐Long; Guo, Zhen; Liu, Xin‐Yuan (Angewandte Chemie International Edition, 2018)
Reported is a novel two‐step ring‐expansion strategy for expeditious synthesis of all ring sizes of synthetically challenging (hetero)aryl‐fused medium‐sized lactams from readily available 5–8‐membered cyclic ketones. This step‐economic approach features a remote radical (hetero)aryl migration from C to N under visible‐light conditions. Broad substrate scope, good functional‐group tolerance, high efficiency, and mild reaction conditions make this procedure very attractive. In addition, this method also provides expedient access to 13–15‐membered macrolactams upon an additional one‐step manipulation. Mechanistic studies indicate that the reaction involves an amidyl radical and is promoted by acid. Growth rings: A two‐step ring‐expansion strategy for expedient synthesis of all ring sizes of synthetically challenging (hetero)aryl‐fused medium‐sized lactams from readily available 5–8‐membered cyclic ketones has been developed. The key step involves an uncommon remote radical (hetero)aryl migration from C to N by C−C bond cleavage under irradiation with visible light.